Maximum instantaneous renewable energy integration of power grids - Huajie Gu (2016 Australasian Universities Power Engineering Conference (AUPEC), 2016)
This paper proposes a probabilistic method to estimate the maximum instantaneous renewable energy integration, subject to the constraints of the rate of change of frequency (RoCoF) and frequency nadir. The minimum system inertia is quantified to ensure a satisfied primary frequency response of a renewable power grid (RPG). Linearized governor response of synchronous generators is then investigated to show that a faster ramping rate can help RPGs integrate more renewable energy and tolerate larger forecast errors. Grid operating codes are also compared to show that the renewable energy integration can be further maximized.